Nitrogenization and Conjugation Reactions - Marwan Taha Abdel Karim Jasim; Doaa Mohsen Muhammad Balbous; Ahmed Safaa Hassoun Ismail; Zahraa jassim mohamed abod; Murtaza khaled Hussein Abboud (Genius Journals, 2024)
This research included an introduction to the development and verification of the analysis method and the role of spectroscopy in it, then to the stability of the drug and its shelf life. Nitrogenation and conjugation reactions, the history of their discovery, their role in pharmaceutical analyzes and their mechanism of action were also explained, as well as A study and review .oso dyes and dizanium salts and their role in this analytical method of some sources shows researchers and those who worked with them for some pharmaceutical drugs and what obstacles they faced in order to know the pros and cons The analytical results were also reviewed from studying the optimal .of the method conditions and the factors affecting this reaction, including the type of acid used, as well as the type of base, the effects of reaction stability, and the time used to complete the reaction to control the quantities added and without wasting the chemicals used
Keywords: spectroscopy; verification; reaction stability